2003
DOI: 10.1016/s1063-4584(03)00055-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cartilage oligomeric matrix protein on mesenchymal chondrogenesis in vitro

Abstract: These data suggest that COMP and BMP-2 signaling converge to regulate the fate of these cells in vitro by affecting both early and late stages of chondrogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 53 publications
(105 reference statements)
1
47
0
Order By: Relevance
“…Additional studies have indicated that COMP can inhibit cell proliferation while enhancing in vitro chondrogenesis (21). Finally, expression of COMP in the presence of BMP2 stimulation can lead to a late increase in apoptosis (21). This latter finding is consistent with the fact that the mutant COMP proteins in multiple epiphysial dysplasia and PSACH appear to mediate apoptosis of chondrocytes in cartilage in vivo (25)(26)(27).…”
mentioning
confidence: 68%
See 3 more Smart Citations
“…Additional studies have indicated that COMP can inhibit cell proliferation while enhancing in vitro chondrogenesis (21). Finally, expression of COMP in the presence of BMP2 stimulation can lead to a late increase in apoptosis (21). This latter finding is consistent with the fact that the mutant COMP proteins in multiple epiphysial dysplasia and PSACH appear to mediate apoptosis of chondrocytes in cartilage in vivo (25)(26)(27).…”
mentioning
confidence: 68%
“…Cells-It has been previously demonstrated that expression of COMP, as either a wild type or mutant form, can affect the level of apoptosis both in vivo and in vitro (21,(25)(26)(27). To explore an effect of COMP on apoptosis, we began transient transfection experiments using a COMP expression plasmid in 293 cells.…”
Section: Comp Enhances Cell Survival In 293mentioning
confidence: 99%
See 2 more Smart Citations
“…COMP, the fifth member of the thrombospondin (TSP) gene family, is a multidomain homopentameric protein comprised of an N-terminal pentamerization domain, an epidermal growth factor (EGF)-like domain, a highly conserved type 3 (calcium-binding) repeat domain, and a C-terminal globular region (Fife and Brandt 1984;DiCesare et al 1994;Adams et al 1995;Smith et al 1997;Hecht et al 1998a;Carlson et al 2008). Recent work suggests that COMP is multifunctional and is involved in (1) regulation of collagen fiber assembly/diameter (Rosenberg et al 1998); (2) interaction with other ECM molecules (Holden et al 2001;Thur et al 2001;Mann et al 2004); (3) regulation of chondrocyte proliferation (Kipnes et al 2003;Xu et al 2007); (4) regulation of apoptosis (Duke et al 2003;Hashimoto et al 2003;Hecht et al 2004); and (5) enhancement of cellular attachment (Chen et al 2005).…”
Section: Introductionmentioning
confidence: 99%